2005
DOI: 10.1002/crat.200410446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cetyl pyridinium chloride additive on crystallization of gypsum in phosphoric and sulfuric acids medium

Abstract: A basic study was carried out to understand effect of Cetyl Pyridinium Cloride (CPC) on calcium sulfate dihydrate (gypsum) crystallization. Induction time was measured under different supersaturation ratios ranging from 1.222 to 1.979. This is the time elapsed between the achievement of supersaturation and the appearance of a solid phase. The results show that, the induction time decreases exponentially with increasing the supersaturation ratio. In addition, the surface energy increases with CPC compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
(10 reference statements)
0
28
0
Order By: Relevance
“…It was found that, the crystal growth rate, the mean diameter, the formation of critical nucleus size free energy and the critical nucleus radius was decreased upon addition of this surfactant, whereas the nucleation rate was increased [20]. Similar to ATMP surfactant, citric acid and tri sodium phosphate inhibit gypsum crystallization while other surfactants assist gypsum and phosphogypsum crystallization [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, the crystal growth rate, the mean diameter, the formation of critical nucleus size free energy and the critical nucleus radius was decreased upon addition of this surfactant, whereas the nucleation rate was increased [20]. Similar to ATMP surfactant, citric acid and tri sodium phosphate inhibit gypsum crystallization while other surfactants assist gypsum and phosphogypsum crystallization [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…They found that citrate does not significantly change the surface energy of the COM crystal nucleate, but citrate does retard the induction time by lowering the supersaturation through citrate complexes formed with the free calcium ions in the solution. The calculations of surface energy, nucleation rate, free energy barrier, and radius of nucleus have also been widely used in other systems such as calcium sulfate crystallization [7][8][9][10][11][12]. Hess also used induction time to explain the inhibitory effect of citrate and the Tamm-Horsfall protein on the COM crystallization by measuring the change of optical density over time [13].…”
Section: Introductionmentioning
confidence: 99%
“…The soluble organic additives such as polyelectrolytes, surfactants, carboxylic, sulfonic and phosphonic acid derivatives are widely used in industrial application to improve gypsum crystallization quality [3,4]. In a study, the effect of cetyl pyridinium chloride (CPC) on gypsum crystallization has been studied by H. El-Shall et al [5]. It was reported that CPC decreases the induction time at all supersaturation ratios studied due to increase of regular crystal growth.…”
Section: Introductionmentioning
confidence: 97%